^{n}√0 = 0.^{n}√1 = 1.^{n}√(*a**b*) =^{n}√*a*⋅^{n}√*b*.^{n}√(*a*/*b*) =^{n}√*a*÷^{n}√*b*.^{1}√*a*=*a*.^{n}√(^{m}√*a*) =^{(mn)}√*a*.^{n}√(*a*^{n}) = |*a*| if*n*is even;^{n}√(*a*^{n}) =*a*if*n*is odd.^{n}√(*a*^{(mn)}) = |*a*|^{m}if*n*is even;^{n}√(*a*^{(mn)}) =*a*^{m}if*n*is odd.^{(mn)}√(*a*^{n}) =^{m}√(|*a*|) if*n*is even;^{(mn)}√(*a*^{n}) =^{m}√*a*if*n*is odd.

Go back to the course homepage.

This web page was written in 2015 by Toby Bartels, last edited on 2015 July 27. Toby reserves no legal rights to it. The permanent URI of this web page is

`http://tobybartels.name/MATH-1100/2015ss/rootrules/`

.